THE IMPORTANCE OF USING SMART DATA TO ANALYZE SKILLS IN THE LABOR MARKET - Pasnicu, Daniela (Annals of Spiru Haret University. Economic Series, 2022)
The needs of the workforce are constantly changing as a result of global concerns about digitization, production automation, the introduction of new technologies and industry 4.0. Therefore, the labor market needs a continuous reassessment of labor skills in the context of digitalization and the industrial revolution. The paper will study the change in perspective of the structure of the employed population by occupational groups and in high-tech economy of Romania compared to UE27 and the most requested skills currently in online job postings in various fields, based on traditional and intelligent data from Cedefop. It is also intended to understand how the use of BigData can facilitate labor market decision-making. The analysis of the skills required in the jobs posted online from various fields in Romania, in 2020, suggests importance of digital and contextual skills having in view that in the top is ,,accessing and analyzing digital data”, followed by ,,working with others” and ,,using digital tools for collaboration, content creation and problem solving”.